An empirical study of the selected consequences of frontline employees' work-family conflict and family-work conflict - Karatepe, Osman M.; Baddar, Lulu (Elsevier Sci Ltd, 2006)
This study developed and tested a research model that examined the effects of work-family conflict (W-FCON) and family-work conflict (F-WCON) on a number of selected consequences using data collected from frontline employees in international five-star chain hotels in Jordan. The results demonstrated that W-FCON exerted a significant positive influence on job stress (JSTRESS), while F-WCON did not. Contrary to the study hypothesis, the results did not provide any empirical support for the significant negative relationship between W-FCON and family satisfaction (FSAT). The findings further revealed that higher F-WCON led to lower FSAT. As expected, high levels of FSAT resulted in increased life satisfaction (LSAT). However, this study failed to find significant negative relationships between conflicts in the work-family interface and LSAT. The results also revealed that JSTRESS was not significantly associated with LSAT. Consonant with the study hypotheses, W-FCON, F-WCON, JSTRESS, and LSAT were found to be significant predictors of turnover intentions (TURNINT). This study reported that the impact of F-WCON on TURNINT was greater than that of W-FCON. Implications for managers and future research directions are presented. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: work-family conflict; family-work conflict; job stress; satisfaction; turnover intentions; frontline employees; Jordan